Uma análise bourdieusiana a respeito da docente na pós-graduação stricto sensu em direito no Brasil frente aos paradigmas da emancipação estrutural e concessão social - Andrade, Thais Machado de (2019)
The thesis explores the relationship established between concessions historically opposed to women by patriarchal culture and the historical process of female emancipations. From the insertion of women as a Subject in the world, from a gender perspective, the research will focus on female praxis in the field of professions, concerning teaching and scientific production, under the question of whether women who have reached eminently masculine spaces represent an emancipation or if they are facing another symbolic form of patriarchal concession. For this, the work is developed under the epistemological bias of Pierre Felix Bourdieu's Structuralism and focuses on analyzing the disparity between the female and male universes in relation to teaching and scientific activity in the field of Law, since official data record a massive presence of women among the masters and doctors. The research was developed with a historiographic study of women in legal teaching, more precisely, their participation in the stricto sensu postgraduate programs in Law in Brazil and the State of Espírito Santo, in order to verify the reality of these women in the field of the symbolic violence produced in the legal field. Thus, it aims to understand the process of female emancipation with a focus on legal field theory as a field of power, male domination and, as an instrument legitimizing the state, as a field that holds the exercise of symbolic violence. And, finally, if this reality would represent the reach of women's structural emancipation or would, in fact, fit into yet another social concession, whose exercise of patriarchal symbolic power persists invisible. Regarding the methodological approach, a qualiquantitative approach was chosen, since the statistical data presented on gender, teaching and legal professions, from the perspective of the symbolic violence postulated by Bourdieu, had to be analyzed qualitatively as well because they represented an inseparable study of historical and social facts.